Pendampingan Usaha Beternak dan Pengolahan Daging Ayam Pada Kelompok Peternak Unggas Di Desa Truwai Kecamatan Pujut Kabupaten Lombok Tengah - Syamsuhaidi Syamsuhaidi; Dwi Kusuma Permatasari; Tapaul Rozi; Sukirno Sukirno; Firmansyah Firmansyah (Jurnal Gema Ngabdi, 2019)
Truwai village, Pujut subdistrict, Central Lombok, is a village that has been designated by government of West Nusa Tenggara provincy as Poultry Village in December 2014.  Truwai village has a strategic geographical position because it is close to the superior tourism area of Kuta and the Mandalika Special Economic Zone (KEK Mandalika).  Based on the potential of the Truwai village, the Truwai village government has a program to increase the efforts to raise domestic poultry and promote the processing of domestic poultry to produce a superior commodity from Truwai that can be used as a souvenir for tourists.  The assistance activities for poultry farming and chicken meat processing training in the Truwai village community aim to increase knowledge and skills in developing the business.  The assistance and training activities were carried out for 5 days in the form of discussions and training in making shredded meat, Truwai grilled chicken, chicken satay and sausage and nuggets.  The result of the activity showed the high enthusiasm of the community in following and processing chicken meat from the beginning to the packaging.  The community expects this assistance activities to continue to be skilled and able to market their products independently